PENGARUH SOCIAL MEDIA MARKETING DAN BRAND AWARENESS TERHADAP REPURCHASE INTENTION KONSUMEN KOSMETIK MAKE OVER DI INDONESIA - Shinta Hestuning; Sari Listyorini; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2025)
Cosmetic products are an essential necessity in embellishing appearance. In this digital age, changing patterns of consumer behavior are influenced by social media marketing and brand awareness, which play a crucial role in shaping repurchase intentions. The study aims to find out the impact of social media marketing and brand awareness on repurchase intention on Make Over consumers in Indonesia. This type of research uses explanatory research using a quantitative approach that is numerical. This study involved 100 respondents. In this study, the sampling technique is using non probability samplings. The data was then processed using SPSS version 25 software. The results of the research show that social media marketing variables have a positive and significant influence on the repurchase intention variable, brand awareness variable has a significant and positive influence over the repurchasing intention. Based on research results, Make Over is suggested to enhance interesting and interactive content, strengthen brand message as well as increase brand visibility, and offer a new product trial or loyalty program that provides incentives for consumers to explore more Make Over products.